Psychological and Organizational Determinants of Healthcare Workers’ Retention in Geriatric Care: A Systematic Review - Ninik Dwi Rahayu; Joni Haryanto; Dianis Wulan Sari (Indonesian Journal of Global Health Research, 2026)
The increasing elderly population increases the demand for geriatric care, while nurse retention remains a major concern due to high workloads, emotional demands, and limited organizational support. High turnover disrupts care continuity and reduces service quality. This systematic review aims to identify key psychological and organizational factors influencing geriatric nurse retention. Method: The review followed PRISMA 2023 guidelines using the PEOS framework. Quantitative cross-sectional studies published between 2015–2025 were retrieved from PubMed, Web of Science, ProQuest, Springer Nature, and ScienceDirect. Study quality was evaluated using the JBI Critical Appraisal Checklist. A total of 13 studies met the inclusion criteria, while 28,076 were excluded. Findings were narratively synthesized to integrate the overall evidence. Thirteen studies from multiple countries identified five main themes: psychological and organizational factors, individual characteristics, student interest, and the interaction between personal and institutional conditions. Intrinsic motivation, social and organizational support, and safe, flexible work environments enhance retention, whereas burnout, excessive workload, and low salary reduce retention intentions.  Geriatric nurse retention is influenced by psychological, social, and organizational factors. Supportive leadership, flexible work policies, and early geriatric education are important for sustaining long-term engagement in geriatric nursing.